The Managerial Dimension of Institutional Quality Assurance in Higher Education Institutions - Iliichuk, Liubomyra (Educological discourse, 2025)
The article analyzes the managerial dimension of institutional quality assurance in higher education institutions through the study of university missions and regulatory documents governing the functioning of internal quality assurance systems under conditions of constant socio-economic and technological changes. The purpose of the study is to identify strategic vectors aimed at ensuring the quality of educational activities and to assess the level of formalization and effectiveness of management mechanisms in internal quality systems. The content analysis method was used, which made it possible to systematically study the content of the missions of higher education institutions and identify key guidelines: training competitive specialists, ensuring the quality of educational services, developing innovative potential, integrating into the international educational space, social responsibility, and supporting regional development. Documentary analysis made it possible to study internal regulations, provisions, and other normative acts that define the principles, procedures, and tools of quality management. The results showed that higher education institutions have comprehensively structured quality systems and responsible departments, but the degree of detail of procedures, the regularity of monitoring, and the systematic nature of their application vary, that affects the effectiveness of the internal quality assurance system. It was concluded that improving the effectiveness of institutional quality assurance requires consistency between declared strategic guidelines and practical management actions, which involves improving mechanisms for monitoring and evaluating results, increasing the transparency of internal processes, and involving a wide range of stakeholders, including higher education seekers, employers, and representatives of the public, in quality assurance procedures.